Kitchen "fun"damentals [videorecording (DVD)]. - Christopherson, Dave (Learning ZoneXpress, 2010)
Teaches the basic techniques used in food preparation. Techniques covered include, handwashing; knife cuts such as large and small dice, julienne, paring, slicing, chop, mince; measuring-dry and liquid; cooking basics-grating, sifting, whipping, rolling, broiling, saute, pan searing, boiling, steaming.